(untitled) (Indian Journal of Child Health, 2024)
Introduction: Prescription errors are common and every step in the process of writing a prescription has the potential for error. These errors can be broadly attributed to the lack of knowledge or lack of skill. Poor legibility, inaccuracy in writing, incomplete prescriptions, omissions, and use of abbreviations are the most common type of errors. Objectives: The primary objective of our study was to assess the completeness and legibility of the prescriptions. This is to estimate the rates of skill-based errors. Secondary objective of this study was to assess the appropriateness of the prescriptions using the pediatrics: Omission of Prescriptions and Inappropriate prescriptions (POPI) tool. Methods: This was a cross-sectional study, conducted in the pediatric outpatient department of a tertiary teaching hospital in New Delhi, India. Prescriptions received by outpatients attending both the general and special pediatric clinics were collected and evaluated using the World Health Organization Guide to Good Prescribing and the Medical Council of India guidelines. Results: A total of 343 prescriptions were assessed, in which 753 drugs were prescribed. A total of 1709 errors were uncovered pertaining to the completeness of the prescription. A majority of the prescriptions were written by postgraduates trainees (206), followed by senior residents (61), consultants (42), and junior residents (20). Abbreviations were used while mentioning the drug names in 53.64% prescriptions. The mean legibility score of all prescriptions was 3.35. Forty (11.66%) prescriptions were found inappropriate as per the International POPI tool. Conclusion: The legibility and completeness are largely overlooked yet crucial to the “Art of Prescription Writing.” They deserve as much awareness and education as the appropriateness of the drugs prescribed. The international POPI tool is a promising tool to analyze the appropriateness of pediatric prescriptions.